(untitled) (Bangladesh Journal of Urology, 2012)
Obstructive uropathy that takes to the renal failure with more frequency in paediatric age is secondary to posterior urethral valve. Recent advance in endoscopy has altered the management and outcome of the patients. Materials and methods: This retrospective study was conducted at National Institute of Kidney Diseases and Urology, Dhaka from July 2005 to December 2009. Total 48 patients were selected for this study among them most were less than 1 year of age and 13 patients (27.08%) had associated vesicoureteric reflux. Most of the patients were presented with dribbling of urine and some were with repeated urinary tract infection and renal failure. Diagnosis was confirmed by Micturating cystourethrogram and Urethrocystoscopy. Results: All the patients were managed by endoscopic fulguration. In most of cases fulguration was primary but in some cases after supportive treatment. Outcome was satisfactory in all cases except one patient (2.08%) developed stricture urethra and 4 patients (8.4%) developed end stage renal diseases. After fulguration 13 patients (27.08%) showed to have associated bladder dysfunction and 4 patients (8.4%) required antireflux surgery. Followup period was 36 months varying between 3 to 48 months. Conclusion: Early and adequate valve fulguration provides the better outcome of posterior urethral valve. BJU 2010; 13(2): 60-63